MITIGASI DAN DAMPAK SOSIAL BANJIR DI KOTA MEDAN: KAJIAN TERPADU TERHADAP FAKTOR PENYEBAB, RESPONS MASYARAKAT, DAN PERAN PEMERINTAH DAERAH - ANDIKA ADITIYA , DINDA AGUSTINA NASUTION; DINDA MAHYUNI SIREGAR, NUR AINI (STKIP Subang, 2025)
This study provides a comprehensive analysis of the flood phenomenon in Medan City, focusing on its causes, social impacts, community responses, and the role of local government in disaster mitigation. Utilizing a qualitative approach with descriptive- analytical methods, data were collected through in-depth interviews and literature review. The findings reveal that floods in Medan are driven by a combination of natural factors such as high rainfall and human factors like land-use change and poor drainage systems. The social impacts include economic losses, health issues, disruption of education, and increased social tensions. Community responses show strong solidarity but also reveal disparities in access to aid. While the local government has implemented various mitigation efforts, they remain suboptimal due to weak inter-agency coordination, budget constraints, and limited community participation. The study recommends a more participatory and sustainable approach to disaster mitigation planning.